Waterborne polyurethanes: A review - Honarkar, Hengameh (Journal of dispersion science and technology, 2018)
Waterborne polyurethanes can be formulated into coatings and adhesives, containing little or no co-solvent, that form films at ambient temperature. They exhibit excellent adhesion to many surfaces including glass and polymeric fibers. These environment-friendly polymers are non-toxic, non-flammable, and they do not pollute the air or produce wastewater. In general, the polyurethanes are hydrophobic in nature and insoluble in water. Therefore, in order to disperse them in water, they must be modified by, for example, incorporating ionic groups and/or non-ionic hydrophilic segments into the polymer structure. In this review paper, types of waterborne polyurethanes, synthesis methods, and applications have been studied.